2018
DOI: 10.1002/jcb.28321
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐802 inhibits cell proliferation and induces apoptosis in human cervical cancer by targeting serine/arginine‐rich splicing factor 9

Abstract: microRNAs (miRNAs) play crucial roles in cancer development and progression by targeting mRNAs for degradation and/or translational repression. micro-RNA-802 (miR-802) has been reported as a tumor suppressor and its deregulation is observed in various human cancers. However, the prognostic value of miR-802 and its underlying mechanisms involved in human cervical cancer are poorly investigated. The purposes of this study were to explore the role of miR-802 in cervical cancer and to clarify the regulation of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
(43 reference statements)
2
31
0
Order By: Relevance
“…miR-802 inhibits cell proliferation and induces apoptosis in human laryngeal cancer by targeting Camp-regulated phosphoprotein 19 [32]. These data further confirm that miR-802 exerted its effects was cell-specific [33,34]. Here, we demonstrated that miR-802 promoted HCC growth.…”
Section: Discussionsupporting
confidence: 78%
“…miR-802 inhibits cell proliferation and induces apoptosis in human laryngeal cancer by targeting Camp-regulated phosphoprotein 19 [32]. These data further confirm that miR-802 exerted its effects was cell-specific [33,34]. Here, we demonstrated that miR-802 promoted HCC growth.…”
Section: Discussionsupporting
confidence: 78%
“…Zhang et al 34 reported that miR-802 promoted cell proliferation and inhibited cell apoptosis in human cervical cancer. 33 MiR-802 also suppressed non-small cell lung cancer development by regulating FGFR1. 34 Consistently, our findings suggested that overexpression of miR-802 suppressed cell growth, migration, and invasion in GC cells.…”
Section: Discussionmentioning
confidence: 97%
“…MiR‐802 has been demonstrated to be a tumor suppressor in multiple cancers. Zhang et al 34 reported that miR‐802 promoted cell proliferation and inhibited cell apoptosis in human cervical cancer 33 . MiR‐802 also suppressed non–small cell lung cancer development by regulating FGFR1 34 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, large amount of evidence has showed that aberrant miR-802 expression is involved in the progression of multiple solid cancers. [11][12][13][14][15][16][17][18][19][20] Noteworthily, the biological role of miR-802 in the tumorigenesis of human cancer mainly depends on cancer type. Numerous studies reported that miR-802 functions as a tumor suppressor in most cancers, including glioblastoma, 12 tongue squamous cell carcinoma, 15 laryngeal, 17 breast, 18 gastric, 20 prostate, 13 ovarian, 16 and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported that miR-802 functions as a tumor suppressor in most cancers, including glioblastoma, 12 tongue squamous cell carcinoma, 15 laryngeal, 17 breast, 18 gastric, 20 prostate, 13 ovarian, 16 and cervical cancer. 19 Nevertheless, miR-802 was demonstrated to function as an onco-miRNA in lung carcinoma 14 and osteosarcoma. 11 Wang et al reported that miR-802 enhanced tumor cells proliferation via suppressing Menin in lung carcinoma; 14 Cao et al showed that miR-802 could promote the proliferation of osteosarcoma cells through regulating p27.…”
Section: Introductionmentioning
confidence: 99%